Cooperative method of listening team type and the power of two type in Islamic religious education learning - Adriantoni, Adriantoni (TARBAWY: Indonesian Journal of Islamic Education, 2022)
Abstract. The purpose of this research is to identify whether the result of the students learning Islamic education using the method of the power of two better than the students leaning Islamic education using the method of power of two in X grade of Sekolah Menengah Atas Negeri (SMAN) 1 Tanah Sepenggal. The typical of this research is Quasi Experimental Research with research plan of randomize control group only design. The population in this research is all of X grade students of SMAN 1 Tanah Sepenggal in 2017/2018. The result of this research illustrates that the average acquisition of experimental class test mark is 80 and control class is 73,6. It is clear that there is a significant difference of learning result between the method of listening team and the method of the power of two in Islamic education lesson.